2021
DOI: 10.1101/2021.02.26.432991
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Xenogeneic Skin Transplantation Promotes Angiogenesis and Tissue Regeneration Through Vitamin D-Activated Trem2+ Macrophages

Abstract: Skin allo- and xenotransplantation are the standard treatment for major burns when donor sites for autografts are not available and have been shown to significantly accelerate wound healing. Although the cellular elements of foreign grafts are rejected, the extracellular matrix components integrate into the wound and may underlie their beneficial effects on wound healing. The molecular mechanisms defining the relationship between the immune response to foreign grafts and their impact on wound healing have not … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 67 publications
0
8
0
Order By: Relevance
“…Trem2 + macrophages promote bacterial clearance, collagen remodeling, and full-thickness skin regeneration during wound healing. [28,63] Here, it was demonstrated that the recruitment of Trem2 + macrophages on Day 3 was statistically higher in the pGel/M-NIR and MpGel-NIR groups, and the MpGel-NIR group maintained this increase on Day 28, indicating the beneficial recruitment of macrophages by pGO. (Figure 5A,B,E,F and Figure S13, Supporting Information).…”
Section: Mpgel Prevents Scar Formation By Recruiting Trem2 + Macropha...mentioning
confidence: 73%
See 3 more Smart Citations
“…Trem2 + macrophages promote bacterial clearance, collagen remodeling, and full-thickness skin regeneration during wound healing. [28,63] Here, it was demonstrated that the recruitment of Trem2 + macrophages on Day 3 was statistically higher in the pGel/M-NIR and MpGel-NIR groups, and the MpGel-NIR group maintained this increase on Day 28, indicating the beneficial recruitment of macrophages by pGO. (Figure 5A,B,E,F and Figure S13, Supporting Information).…”
Section: Mpgel Prevents Scar Formation By Recruiting Trem2 + Macropha...mentioning
confidence: 73%
“…The recruitment of Trem2 + macrophages regulates collagen remodeling and promotes angiogenesis. [28] Damaged endothelial progenitor cells and low cytokines limit angiogenesis in diabetic wounds. [67] Moreover, pathological angiogenesis can result in functional ischemic wounds.…”
Section: Mpgel-nir Results In Vascularizationmentioning
confidence: 99%
See 2 more Smart Citations
“…Using scRNA-seq, they found a distinct subpopulation of macrophages with a high expression of the lipid receptor Trem2 (triggering receptor expressed on myeloid cells), which demonstrated the great effectiveness in alleviating wound repair. [73] Similarly, in the study by Sommerfeld et al, murine volumetric muscle injuries received treatment with ECM or synthetic biomaterial. CD45 + CD64 + F4/80 hi+ macrophages were sorted for single cell analysis.…”
Section: Recent Advances In Elucidating the Mechanisms Of Fbrmentioning
confidence: 99%